Ultrafast internal conversion dynamics of bilirubin bound to UnaG and its N57A mutant. Issue 5 (22nd January 2019) - Cao, Xiaodan; Zhang, Changcheng; Gao, Ziheng; Liu, Yangyi; Zhao, Yuzheng; Yang, Yi; Chen, Jinquan; Jimenez, Ralph; Xu, Jianhua
Abstract : High fluorescence quantum yield of BR in UnaG is due to direct hydrogen bonds to the endo -vinyl dipyrrinone moiety. Abstract : Fluorescent proteins (FPs) have become fundamental tools for live cell imaging. Most FPs currently used are members of the green fluorescent protein super-family, but new fluorophores such as bilin-FPs are being developed and optimized. In particular, the UnaG FP incorporates bilirubin (BR) as a chromophore, enhancing its fluorescence quantum yield by three orders of magnitude relative to that in solution. To investigate the mechanism of this dramatic enhancement and provide a basis for further engineering of UnaG and other tetrapyrrole-based fluorophores, we performed picosecond fluorescence and femtosecond transient absorption measurements of BR bound to UnaG and its N57A site-directed mutant. The dynamics of wt-UnaG, which has a fluorescence QY of 0.51, are largely homogeneous, showing an excited state relaxation of ∼200 ps, and a 2.2 ns excited-state lifetime decay with a kinetic isotope effect (KIE) of 1.1 for D2 O vs. H2 O buffer. In contrast, for UnaG N57A (fluorescence QY 0.01) the results show a large spectral inhomogeneity with excited state decay timescales of 47 and 200 ps and a KIE of 1.4. The non-radiative deactivation of the excited state is limited by proton transfer. The loss of direct hydrogen bonds to the endo -vinyl dipyrrinone moiety of BR leads to high flexibility and structural heterogeneity of UnaG N57A, as seen in the X-ray crystal structure.